PET imaging of synaptic vesicle glycoprotein 2 subtype A for neurological recovery in ischemic stroke. - Luo, Xiaoyun; Jin, Chentao; Chen, Hetian; Niu, Jiaqi; Yu, Congcong; Dou, Xiaofeng; Wang, Jing; Wen, Junjie; Zhang, Hong; Tian, Mei; Zhong, Yan (European Journal of Nuclear Medicine & Molecular Imaging, 2024)
Purpose: [18F]SynVesT-1 is a novel radiopharmaceutical for assessing synaptic density in vivo. This study aims to investigate the potential of [18F]SynVesT-1 positron emission tomography (PET) in evaluating neurological recovery in the rat model of ischemic stroke, and to compare its performance with [18F]FDG PET. Methods: Sprague-Dawley rats were subjected to photothrombotic cerebral infarction, and safinamide was administered intraperitoneally from day 3 to day 14 post-stroke to alleviate neurological deficits. Cylinder test and forelimb placing test were performed to assess the neurological function. MRI, [18F]SynVesT-1 PET/CT and [18F]FDG PET/CT imaging were used to evaluate infarct volume, synaptic density, and cerebral glucose metabolism pre- and post-treatment. [18F]SynVesT-1 and [18F]FDG PET images were compared using Statistical Parametric Mapping (SPM) and region of interest (ROI)-based analysis. Post-mortem histological analysis was performed to validate PET images. Results: Safinamide treatment improved behavioral outcomes in stroke-damaged rats. Both [18F]SynVesT-1 and [18F]FDG PET detected stroke-induced injury, with the injured region being significantly larger in [18F]FDG PET than in [18F]SynVesT-1 PET. Compared with the saline group, radiotracer uptake in the injured area significantly increased in [18F]SynVesT-1 PET after safinamide treatment, whereas no notable change was observed in [18F]FDG PET. Additionally, [18F]SynVesT-1 PET imaging showed a better correlation with neurological function recovery than [18F]FDG PET. Post-mortem analysis revealed increased neuronal numbers, synaptic density, and synaptic neuroplasticity, as well as decreased glia activation in the stroke-injured area after treatment. Conclusion: [18F]SynVesT-1 PET effectively quantified spatiotemporal dynamics of synaptic density in the rat model of stroke, and showed different capabilities in detecting stroke injury and neurological recovery compared with [18F]FDG PET. The utilization of [18F]SynVesT-1 PET holds promise as a potential non-invasive biomarker for evaluating ischemic stroke in conjunction with [18F]FDG PET.